Assessment Of Noise Pollution Exposed To Workers In Furniture And Metal Factory - Muhamad, Edy Mustaqim (Universiti Sains Malaysia, 2019)
Noise pollution is a major problem around the world especially come from industry area. This research was conducted at the industry which is furniture and metal factory because recently no or less studies on noise exposure at Pulau Pinang industry in Malaysia. Nowadays, noise on workers’ health always a subject of debate. This study focuses on determine the source of noise at workplace. Noise produced by contact between the machine and the working surface. The mechanisms of noise depend on the noisy operation and equipment. Most of noise source from this study are from machinery and processes of product such as cutting machine, drilling machine and operation forklift. This study investigate the noise level in the workplace exposed to the workers and carried out the field work by using sound level meter type CR1710. Noise level from industry mostly exceeding the limits and obviously affects the hearing of the workers. Based on the objective of this study, the result of highest noise level in the observation is 91.0 dB(A) which is in danger zone and exceeding the upper limit for noise exposure with 85 dB for the duration 8 hours of work per day. Then, the lowest noise level is 54.2 dB(A) and it is considering as safe zone and under the control condition of noise. This study aims to obtain noise level map to visualize the distribution of noise pollution, which can be combined with geographical information system and different noise source contribution analysis.